RESPONS PERTUMBUHAN DAN PRODUKSI PADI SAWAH METODE SRI ( SYSTEM OF RICE INTENSIFICATION ) TERHADAP PEMBERIAN PUPUK ORGANIK DAN ANORGANIK - Andrew Paat; Jeanne M. Paulus; Doortje M.F. Sumampow; Deanne A. Kojoh (COCOS, 2015)
ABSTRACTThis research aims to study the response of growth and production paddy rice methods sri (system of rice intensification) toward granting the organic and inorganic fertilizer that implemented in the village of Tara-Tara II, subdistrict tomohon west for 5 months start from march to august 2013. This study uses a randomized block design group (RAK) and the faktor the meticulous is a kind of organic fertilizers combined with the treatment of inorganik fertilizers (NPK) consists above P0 = 100 % NPK, P1 = organic fertilizers market waste + 40% NPK, P2 = organic fertilizers plant calliandra + 40% NPK, P3 = organik fertilizers rice straw + 40% NPK, P4 = organic fertilizers mixture + 40% NPK.awarding Organic and inorganic fertilizer give influence the growth and production paddy rice methods SRI (System of Rice Intensification). treatment p3 is the best results high toward rice plants with a value of 96.7, but not significantly different with treatment P1, P2, and P4. the influence most well toward the number of produktive tillers and the persentage of grain pithy/ panicles by value 96,58%. Treatment p3 derive the best results in a variable number of grain / panicle with a value of 234.0, but not significantly different with treatment P1 and P2. treatment P4 is the best result toward weight 1000 grain of dry grain harvest with a value of 28.24 grams, although not significantly different with treatment P1, P2, and P3. on variables outcome dry grain harvest the / plot, the best result is the treatment P3 with a value of 8.0 kg, although not significantly different from P2 treatment.keywords: Paddy rice, SRI (System of Rice Intensification), organic fertilizers and inorganic fertilizers.